Kajian Sosiolinguistik terhadap Persepsi Kekasaran dalam Gaya Berbicara Masyarakat Makassar - Andi Nurrahmi Azani Alwi; Arief Fiddienika; Dyah Adila Perdana (Laboratory of Anthropology Department, Faculty of Humanity, Halu Oleo University, 2025)
This research examines the perception of roughness in the speaking style of the Makassar community through a sociolinguistic approach. The distinctive speaking style of the Makassar community, characterized by high intonation, assertive tone, and the use of address terms such as